Genome size and identification of abundant repetitive sequences in Vallisneria spinulosa - Feng,RuiJuan; Wang,Xin; Tao,Min; Du,Guanchao; Wang,Qishuo (PeerJ, 2017)
Vallisneria spinulosa is a freshwater aquatic plant of ecological and economic importance. However, there is limited cytogenetic and genomics information on Vallisneria. In this study, we measured the nuclear DNA content of Vallisneria spinulosa by flow cytometry, performed a de novo assembly, and annotated repetitive sequences by using a combination of next-generation sequencing (NGS) and bioinformatics tools. The genome size of Vallisneria spinulosa is approximately 3,595 Mbp, in which nearly 60% of the genome consists of repetitive sequences. The majority of the repetitive sequences are LTR-retrotransposons comprising 43% of the genome. Although the amount of sequencing data used in this study was not sufficient for a whole-genome assembly, it could generate an overview of representative elements in the genome. These results will lay a new foundation for further studies on various species that belong to the Vallisneria genus.
Keywords: Genome size; C value; Repetitive sequences; Vallisneria spinulosa; RepeatExplorer